26 Patient outcome in the danish quality database for prehospital emergency medical services. (26th April 2019) - Christensen, HC; Christensen, EF; Berlac, PA
Abstract : Background: A national Prehospital Quality Database 1 has been established in Denmark, and most quality indicators reported are reflecting the administration of the service. In the effort to change the perspective of the register toward patient-centered care and outcomes, cardiac arrest data has been sought from the national digital patient chart used by all medical personal in the EMS. The gold standard for comparison was The Danish Cardiac Arrest Register based on paper reports. Method: The study population consists of all emergency patients, where the entrance to health care is a 1-1–2 call forwarded to one of the five regional emergency medical coordination centers in Denmark (300, 000–3 50 000 annually). The use of medical data on patients treated with cardiac arrest was collected directly from the medical charts to compare level of registration and quality of treatment. These data were available for 2016 and 2017. Results: From the medical charts we extracted 2576 patients in 2017 with witness cardiac arrest with 28.0% (n=?) had ROSC. Among patients receiving CPR 48.6% (n=) achieved ROSC. Correspondingly in 25.1% and 47.5% in 2016. In 2016 DHR reported an incidence of 66 per 1 00 000 inhabitants, where the new data yields 85 per 1 00 000. This suggests an underreporting to the register during the time of paper reports. Conclusion: National monitoring of health quality should reflect patient outcome. Extracting data directly from the medical charts is not without challenges but is feasible and will help to raise the standard of care. Reference: Christensen-EF, Berlac-PA, Nielsen-H, Christiansen-CF: The Danish quality database for prehospital emergency medical services. Clinical Epidemiology 2016:8667–671. Conflict of interest: None. Funding: None.